Hubungan Customer Relationship Marketing (CRM) terhadap Loyalitas Pasien di Instalasi Rawat Inap RS Stella Maris Kota Makassar - Nurul Hidayah Nur (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The development of new and old patient visits at the inpatient installation of Stella Maris Hospital, Makassar City in 2022-2024, the number of new patient visits increased, namely from 2,586 visits to 11,005 visits and old patient visits from 2022-2024 also increased by 3,720 visits to 26,501 visits. However, it is different from the bed utilization rate (BOR) at Stella Maris Hospital, Makassar City, from 2016-2018 the results were 48.31%, this figure is still below the parameters of the Indonesian Ministry of Health (2005) which is 60% -85%. This study aims to determine the relationship between customer relationship marketing (CRM) and patient loyalty at Stella Maris Hospital, Makassar City. This type of research is quantitative with a cross-sectional approach. The number of samples in this study was 85 respondents using the Purposive Sampling sampling technique. Based on the results of the Kendall Tau correlation test, a p-value of 0.003 <α (0.05) was obtained, which means that there is a significant relationship between customer relationship marketing and patient loyalty, and a correlation coefficient of 0.321 was obtained, which means that the relationship is quite close. The conclusion of this study is that there is a relationship between customer relationship marketing and patient loyalty in the inpatient installation of Stella Maris Hospital, Makassar City. The suggestion given by the researcher is that there is an effort from the marketing management of Stella Maris Hospital, Makassar City to continue to improve customer relationship marketing strategies in order to increase patient loyalty.